Relationship between tempo, type and effect of attack in male young volleyball players from high competitive level - José Cícero Moraes; Natália Neiva Ferreira; Pablo Juan Greco; Isabel Mesquita; Gustavo Costa (Universidade Federal de Santa Catarina, 2010)
At present, the role the attack plays in a high level volleyball game and team performance is unquestionable. This sports modality is characterized by fast, precise and powerful attacks that require technical control and the ability to adapt to situational constraints of the game. Thus, the objective of this study was to examine the relationship between time and type of attack and the effect of the attack in national junior male volleyball teams. For this purpose, 1191 attack actions of national teams participating in the World Junior Championship were analyzed. The most recurrent effect of attack was the point, and faster and powerful attacks occurred more frequently. The fastest game favored gaining of a point and the powerful attack emerged from the need to overlap the opponent's defensive system